PEMETAAN LAHAN DAERAH IRIGASI KRITIS DI UPTD PENGAIRAN PUJON KABUPATEN MALANG - Kiki Frida Sulistyani; Galih Damar Pandulu (Universitas Tribhuwana Tunggadewi Malang, 2017)
This study expects Mapping Critical Area of Irrigation Land in UPTD Pujon to determine the criticality of the watershed is in the context of decision making related to issues of conservation and watershed management, especially in the handling of the floods and damage to watersheds in order to maintain food security . The purpose of this study is the availability of topographic maps, land cover map, prone to flooding map, Critical Areas Map UPTD Pujon Territory. Results from this study is the existence of maps and data as well as information related to critical areas and disaster-prone of districts in Malang, especially the working area UPTD SDA and Irrigation of Pujon. The research method used 1. Assessment Analysis of disaster prone regions namely climatic conditions, from the monthly climatological data that include wind speed, temperature, humidity, solar radiation and daily rainfall data. Assessment is for the provision of value in the slope class, soil texture class, the land cover and rainfall class. Weighting is giving value for each parameter influenced. 2. Analysis of the level of vulnerability and the risk of flooding to the determination of the value of vulnerability and risk of an area against floods. The results of this study can be found in the area of critical land Pujon districts, while the level of vulnerability to flooding obtain flood prone land area of 46.87 km2 and is very prone to flood an area of 2.89 km2. From this study can be used as the basis for decision-making on land use data changes so that the future use of land could be more ideal and friendly environmentalKata kunci: